Protein expression of Fragile Histidine Triad and cyclooxgenase-2 in serrated neoplasia of the colorectum - Tamoto, Akihiro (Oncol Lett, 2017)
The adenoma-carcinoma sequence (ACS) and the serrated pathway are two distinct developmental routes leading to the formation of colorectal carcinoma (CRC). However, the mechanism triggered by the serrated pathway remains unclear. Therefore, to clarify the molecular and clinicopathological characteristics of the serrated tumorigenic pathway, immunohistochemistry was used to examine the expression of Fragile Histidine Triad (FHIT), cyclooxygenase-2 (COX-2), MutL homolog 1 (MLH1), MutS protein homolog 2 (MSH2) and P53 in endoscopically resected samples of 62 serrated polyps. These samples included 20 hyperplastic polyps (HPs), 16 traditional serrated adenomas (TSAs), 26 sessile serrated adenoma/polyps (SSA/Ps), 20 non-serrated adenomas, 20 carcinoma in adenomas (CIAs) and 18 early pure CRCs without any adenoma component (EPCs). FHIT expression was markedly reduced or absent in 50% of TSA samples, 92.3% of SSA/Ps and 44% of EPCs, but only rarely in HPs, non-serrated adenomas and CIAs. COX-2 expression was more common in non-serrated adenomas compared with in serrated polyps, and was present in 25 and 3.2% of the cases respectively (P<0.01). Furthermore, COX-2 expression was more frequent in CIAs (60%) compared with in EPCs (22.2%; P<0.05). The incidence of negative COX-2 expression was higher in FHIT-negative SSA/Ps compared with in FHIT-positive SSA/Ps (P=0.08). A total of 16.7% of EPC samples and 11.5% of SSA/Ps demonstrated a loss of MLH1/MSH2 expression, but none of the other tumor types did. P53 overexpression was significantly increased in EPC (77.8%) and CIA (60%) samples compared with in HP (0%), TSA (6.6%), SSA/P (0%) and non-serrated adenoma (10%) samples (P<0.01). These findings demonstrated that there are different expression patterns between the serrated pathway and ACS, indicating that aberrant FHIT and inhibited COX-2 expression may be associated with serrated tumorigenesis. In addition, this data indicated that EPC may contain tumors derived from the serrated pathway as well as ACS.